A new species of Prosopanche (Hydnoraceae) from northeastern Brazil - Machado, Ricardo Ferreira; de Queiroz, Luciano Paganucci (Phytotaxa, 2012)
Prosopanche caatingicola, a new species from seasonally dry forests of northeastern Brazil, is described. It was found as a root parasite of Parapiptadenia zehntneri, Mimosa ophthalmocentra and Calliandra depauperata (all Fabaceae; Mimosoideae). It is closely related to P. bonacinai, a species from northern Argentina, Rio Grande do Sul (Brazil) and Paraguay, and differs from that species mostly by smaller flowers, shape of its deeply bilobed staminodial appendages and anthers with 5–8 thecae.